The effect of periodic modulation on the aperiodic current in linear-scan and cyclic voltammetries - Gavaghan, David J; Myland, Jan C; Oldham, Keith B (Journal of electroanalytical chemistry (Lausanne, Switzerland), 2001)
The modulation of a ramped potential applied to a voltammetric electrode evokes two responses: a quasiperiodic ‘ac’ current of the same periodicity as the modulation, and a perturbation of the underlying dc current. The latter is the subject of this article. Reasoning by analogy with an analytical result for reversible square-wave-modulated linear-potential-scan voltammetry, a sequence of credible arguments has allowed prediction of the dc current for modulations of any waveform and of any amplitude. Applications to staircase voltammetry and to modulated cyclic voltammetry are included.